Estudio de prefactibilidad para la instalación de una planta productora de cremas exfoliantes a base de sales minerales del mar muerto y aceite de jojoba - Córdova Merzthal, María Eugenia (2018)
The objective of the study is not only to evaluate and determine technical and financial viability, but also economic, social and market viability; to demonstrate that this proposal contains added value as a project in general.